THE EFFECTIVENESS OF USING QUIZIZZ LEARNING MEDIA TO IMPROVE HISTORY LEARNING ACHIEVEMENT FOR ACADEMIC YEAR 2022/2023 - Ismi Lestari, Nurul (CV. Fahr Publishing, 2023)
The low achievement of studying history at SMA Negeri 3 Bantul is still a problem that exists today. There are still students who score below the minimum Minimum Completeness Criteria, making teachers have to think about innovations that will be implemented in learning in order to improve student history learning achievement. This study aims to see the effectiveness of using Quizizz learning media to improve student history learning achievement at SMA Negeri 3 Bantul for the 2022/2023 school year. This research uses quantitative methods with the type of True Experimental design and post-test-only control group design research design with a population of grade XI IPS 1 and MIPA 2 SMA Negeri 3 Bantul for the 2022/2023 academic year. The sample used in this study was the entire population that had been determined. The research instrument this time uses tests which are divided into Pre-test and Post-test and observation sheets for learning implementation. Data testing using the help of IBM SPSS 21 Softwere. Test the hypothesis using the Wilcoxon Test. The results showed that (1) Quizizz learning media was not effective in increasing students' historical learning achievement with Asymp scores. Sig. 2 tailed 0.009 which is 0.009 < 0.05. (2) Quizizz learning media is not effective in increasing students' history learning achievement with Asymp scores. Sig. 2 tailed 0.000 where 0.000 < 0.05. (3) Quizizz learning media is no more effective than conventional learning media to improve students' history learning achievement with Asymp scores. Sig. 2 tailed 0.002 where 0.002 < 0.05 The use of learning media should be used as ice breaking during learning. Research should be carried out with maximum effort in order to get maximum data results. Class selection as a sample in research should be done by referring to big data on student scores so that class selection can be decided appropriately and equally. Keywords: Effectiveness, Quizizz Learning Media, Learning Achievement